Răspuns :
3x(x-7)=6x;
3x²-21x=6x;
3x²-21x-6x=0;
3x²-27x=0;
∆=b²-4ac=729;
x1,2=(-b±√∆)/2a;
=>x1=(27+27)/6=54/6=9;
=>x2=(27-27)/6=0/6=0;
3x²-21x=6x;
3x²-21x-6x=0;
3x²-27x=0;
∆=b²-4ac=729;
x1,2=(-b±√∆)/2a;
=>x1=(27+27)/6=54/6=9;
=>x2=(27-27)/6=0/6=0;
3x(x-7)=6x
3x(x-7) - 6x = 0
3x(x-7) - 3•2x = 0
3x(x-7) - 3x•2 = 0
3x[(x-7) -2] = 0
3x(x-9)= 0
3x = 0 => x = 0
sau
x-9 = 0 => x = 9
=> S = {0,9}
3x(x-7) - 6x = 0
3x(x-7) - 3•2x = 0
3x(x-7) - 3x•2 = 0
3x[(x-7) -2] = 0
3x(x-9)= 0
3x = 0 => x = 0
sau
x-9 = 0 => x = 9
=> S = {0,9}